Risk analysis of impacting people and/or equipment due to rockfall - Bermedo, E; Schellman, M; Diaz, D (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
A risk analysis methodology due to rockfall is presented, in contrast to the conventional analysis that only considers the probability that a rock falling from certain place may pass over a containment barrier. The risk analysis methodology will also consider variables that are inherent in the site and specific conditions of the same such as for example the probability that rockfall may take place, exposure time, etc. The final value obtained will be a probability associated with one or more fatalities, which will be compared with a criterion defined to assess the risk of the sector.
Keywords: rockfall; risk analysis; fatalities